2014
DOI: 10.1016/j.nedt.2014.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Informal mobile learning in nurse education and practice in remote areas—A case study from rural South Africa

Abstract: s u m m a r y a r t i c l e i n f o Background: With the proliferation of portable digital technology, mobile learning is becoming increasingly popular in nursing education and practice. Most of the research in this field has been concentrated on small-scale projects in high income countries. Very little is known about the ways in which nurses and midwives use mobile technology in remote and resource poor areas in informal learning contexts in low and middle income countries. Objectives: To address this gap, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 35 publications
1
44
0
1
Order By: Relevance
“…However, as the Internet penetrates further into these countries, indications are that mobile technology will be a great treasure for education, especially in Africa. This can be validated by the recent studies of Pimmer et al (2014) who found, contrary to Valk et al (2010) that mobile phones are capable of enhancing learning in rural and low-income areas. This could be ascribed to the escalating access to mobile devices.…”
Section: Implications For M-learning In Africamentioning
confidence: 61%
See 1 more Smart Citation
“…However, as the Internet penetrates further into these countries, indications are that mobile technology will be a great treasure for education, especially in Africa. This can be validated by the recent studies of Pimmer et al (2014) who found, contrary to Valk et al (2010) that mobile phones are capable of enhancing learning in rural and low-income areas. This could be ascribed to the escalating access to mobile devices.…”
Section: Implications For M-learning In Africamentioning
confidence: 61%
“…Pimmer et al (2014) observed in the South African study that the nurses had some restrictions in the use of mobile devices and social media. In some instances, they were banned from using these devices.…”
Section: Implications For M-learning In Africamentioning
confidence: 99%
“…Alvarez, Sasso, and Iyegar (2015) studied mobile virtual learning and nursing students' evaluation of acute pain; it appears that technology has made a positive contribution to learning acute pain assessment using mobile devices. Pimmer et al (2014) reported that nursing students use mobile learning as an effective problem solving method in the process of solving problems related to the illness. It shows that the use of technology is applicable in higher education in nursing and that it creates an innovative process for teaching / learning by influencing the ways in which learners develop knowledge (Alvarez et al, 2015).…”
Section: Extended English Abstractmentioning
confidence: 99%
“…12 In rural South Africa a group of nurses reported several 'organically grown' mobile-telephone-based practices facilitating learning, including reflective practice, emotional support and teaching in unpredictable situations. 13 The success of mLearning in the developing world has been well documented in African rural healthcare workers treating infectious diseases, 9,10,12 but only one study, on nurses screening for breast cancer in Iran, was found in a hospital-based setting. 11 Documentation of its efficacy in an African hospital-based scenario was not found and it has not been proved in anaesthesia nurses.…”
Section: Introductionmentioning
confidence: 99%